Gen Z Nursing Students' Usage, Perception and Satisfaction with Facebook for Educational Purposes: Tool for Learning or Distraction - Ryan Michael Oducado (Indonesian Nursing Journal of Education and Clinic, 2019)
Introduction: Gen Z has started to enter the portals of nursing classrooms. They are technology and socially-savvy consumers who grew up in the world of internet and smartphones. However, little is known about this generation, particularly among nursing students and how they use Facebook for academic purposes. The purpose of this study was to determine nursing students' usage, perception, and satisfaction with Facebook for educational purposes Methods:A descriptive, cross-sectional research design was used. A total of 113 conveniently chosen nursing students in a Nursing College in the Philippines participated in the survey. Data were collected using an adopted questionnaire administered via online survey. Descriptive and inferential statistical tools were used to analyze the data. Results: Results indicated that majority of nursing students moderately (M=3.58) use Facebook for educational purposes to communicate, collaborate, and share academic or learning materials. They generallyhad a good perception of (M=4.36) and were highly satisfied (Mean=3.95) with using Facebook for educational purposes. The main challenge reported by 81.42% of nursing students in the use of Facebook was distraction from other Facebook contents. There was a significant positive relationship between usage and perception (p=.000) likewise between satisfaction and recommendation in the use of Facebook for educational purposes (p=.000). Conclusions:While Facebook showcases promising potential as a learning tool, challenges associated with its use in nursingeducation must be properly addressed. Careful consideration a
Keywords: 330; Facebook; Gen Z; nursing education; nursing students; social media; e-learning; online learning